Poor nutritional status is associated with other geriatric domain impairments and adverse postoperative outcomes in onco-geriatric surgical patients – A multicentre cohort study. Issue 7 (July 2016) - Huisman, M.G.; Veronese, G.; Audisio, R.A.; Ugolini, G.; Montroni, I.; de Bock, G.H.; van Leeuwen, B.L.
Abstract: Background: Nutritional status (NS), though frequently affected in onco-geriatric patients, is no standard part of a geriatric assessment. The aim of this study was to analyse the association between a preoperatively impaired NS and geriatric domain impairments and adverse postoperative outcomes in onco-geriatric surgical patients. Methods: 309 patients ≥70 years undergoing surgery for solid tumours were prospectively recruited. Nine screening tools were preoperatively administered as part of a geriatric assessment. NS was based on BMI, weight loss and food intake. Odds ratio's (OR) and 95% confidence intervals (95% CI) were estimated using logistic regression analysis. The occurrence of 30-day adverse postoperative outcomes was recorded. Results: At a median age of 76 years, 107 patients (34.6%) had an impaired NS. Decreased performance status and depression were associated with an impaired NS, when adjusted for tumour characteristics and comorbidities (ORPS>1 3.46; 95% CI 1.56–7.67. ORGDS>5 2.11; 95% CI 1.05–4.26). An impaired NS was an independent predictor for major complications (OR 3.3; 95% CI 1.6–6.8). Ten out of 11 patients who deceased had an impaired NS. Conclusion: An impaired NS is prevalent in onco-geriatric patients considered to be fit for surgery. It is associated with decreased performance status and depression. An impaired NS is a predictor for adverse postoperative outcomes. NS should be incorporated in a geriatric assessment.